Understanding the barriers to nurses' participation in research: an exploration of constraining factors in Lithuania - Viktorija Piscalkiene; Inga Mikutaviciene; Daiva Bartusiene; Lijana Navickiene (Millenium)
Introduction: Nurses face barriers and challenges in participating in scientific research, with a focus on the gap between research and clinical practice. Although nursing research is essential for improving patient care and strengthening evidence-based practice (EBP), nurses' involvement in research in Lithuania remains limited.